2019
DOI: 10.1080/01932691.2019.1626249
|View full text |Cite
|
Sign up to set email alerts
|

The effect of monoethanolamine as stabilizing agent in Uncaria gambir Roxb. mediated synthesis of silver nanoparticles and its antibacterial activity

Abstract: The development of an economic and eco-friendly approach of silver nanoparticles synthesis is an important issue due to its wide application, especially in biomedical applications. In present study, an eco-friendly method and size controlling is developed to synthesize silver nanoparticles using Uncaria gambir Roxb. and monoethanolamine (MEA) as bioreducing agent and stabilizing agent, respectively. The green synthesized silver nanoparticles are characterized using UV-Vis spectroscopy, X-ray diffraction (XRD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
(60 reference statements)
0
11
0
2
Order By: Relevance
“…Salah satu tumbuhan komoditas industri Indonesia yang telah dimanfaatkan sebagai sumber agen bio-reduksi dalam mensintesis NP-Ag adalah tumbuhan gambir (Uncaria gambir Roxb.) [8,9]. Lebih lanjut, rendahnya tingkat kestabilan dan aktifitas koloid NP-Ag masih menjadi kendala dalam aplikasi dilapangan.…”
Section: Analisis Kontenunclassified
“…Salah satu tumbuhan komoditas industri Indonesia yang telah dimanfaatkan sebagai sumber agen bio-reduksi dalam mensintesis NP-Ag adalah tumbuhan gambir (Uncaria gambir Roxb.) [8,9]. Lebih lanjut, rendahnya tingkat kestabilan dan aktifitas koloid NP-Ag masih menjadi kendala dalam aplikasi dilapangan.…”
Section: Analisis Kontenunclassified
“…Antibacterial activity of the samples was screened against pathogen bacteria, i.e. Staphylococcus aureus and Escherichia coli as following procedure [10,27] : Nutrient agar (NA) media was prepared by dissolving an amount of agar in distilled water, boiled, and sterilized in an autoclave at 121 C for 20 min, and then cooled until 45 C. Petri dishes for antibacterial assay were sterilized in an autoclave. Bacterial was subcultured in 5 mL of sterile distilled water for overnight.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Uncaria gambir Roxb. leaves were taken from the experimental garden, Andalas University, Padang, Indonesia and extracted using the method of Labanni et al [16]. Fresh leaves were washed, dehydrated by shade drying, and mashed up to obtain powder.…”
Section: Synthesis Of Hap-agnps Compositementioning
confidence: 99%
“…Several studies have reported that in the stabilizing mechanism of silver nanoparticles by alkanolamine compounds, an electrostatic interaction occurs between free electron pairs from nitrogen and positively charged AgNps, resulting in a protective monolayer. This monolayer then caps nanoparticles to avoid excessive fusion, hence controls the growth and size of nanoparticles [16,25,26]. It is assumed that hydroxyl groups of alkanolamine compound obstruct further interaction among silver nanoparticles.…”
Section: Transmission Electron Microscopy Analysismentioning
confidence: 99%
See 1 more Smart Citation